Discovering metabolic indices for early detection of squash (Cucurbita maxima) storage quality using GC–MS-based metabolite profiling. (1st April 2016) - Okazaki, K.; Kimura, Y.; Sugiyama, K.; Kami, D.; Nakamura, T.; Oka, N.
Highlights: Changes in water-soluble metabolites of squash during storage were analyzed. Arabinose and xylose levels were highly correlated with squash storage quality. The rank order of cultivars by arabinose and xylose concentration was stable during the first 3 months. Based on the metabolite analysis, a new reliable indicator of storage quality was proposed. Abstract: Squash ( Cucubita maxima ) cultivars with good storage qualities are needed for breeding to improve poor crop supply during winter in Japan. We measured changes in squash constituents during different storage periods to identify compounds that were suitable to be used as indices of storage quality. Principal components analysis of compounds at 1–5 months after harvest showed that PC1 scores were lower for cultivars with a higher rather than lower SQ (storage quality) ranks. Partial least-squares regression analysis was performed using the peak areas of all compounds identified from the 15 cultivars at 1 month after harvest as explanation variables and SQ as the target variable. Variable influence on projection scores and rank correlation coefficients were higher for arabinose and xylose, which showed less temporal change during the storage period; hence, they were considered to be suitable indicators for storage evaluation. These data will be useful for future studies aiming to improve storage quality of squash.